When the Opposition Dominates the Conversation (Twitter Network Analysis about the Controversial Indonesian Constitutional Court Decision) - Priyansyah, Rifki Nur; Sulaiman, Rudi Reynal; Firdaus, Ferdi Raihan (JURNAL KOMUNIKASI INDONESIA, 2024)
The Constitutional Court of Indonesia decided to grant a request of the Deputy Chairman of the Corruption Eradication Commission (KPK) to extend the term of office of the KPK from 4 years to 5 years. This brought up public attention on Twitter, including members of the House of Representatives (DPR). Social network analysis was used to discover how the discussion appeared on the Twitter network and the actors involved (using indegree, outdegree, and betweenness centrality derived from graph theory). The Netlytic program recorded 6,195 uploads from May 25, 2023, to June 1, 2023. the Gephi application detects 3377 nodes and 5050 edges. The analysis showed a domination of words with negative nuances. In terms of indegree, news media still stands as an important resource for the Twitter users, although the space for regular users being popular is widely open. Regular users also were able to participate more actively with less restriction. However, institutions or politicians were not engaged in the discussion. These findings should be an evaluation for the government in managing their relationship with the public.